Intercultural communication in Kazakhstan and Uzbekistan: traditions and prospects (Journal of Philosophy Culture and Political Science, 2018)
Strengthening of mutually beneficial relations with Uzbekistan is one of the main foreign policy directions of Kazakhstan in Central Asia region. From an objective point of view, between Kazakhstan and Uzbekistan, there are all prerequisites for large-scale interaction, cooperation, coordinated policy in the region and world. Authors research modern intercultural communication state in Kazakhstan and Uzbekistan. It is complicated, but developing. This analysis let us show intercultural communication possible prospects in observable countries. Key words: Kazakhstan, Uzbekistan, culture, intercultural communication, collaboration.